PEREKAYASAAN FEMINIMITAS TOKOH UTAMA DALAM NOVEL FEMALE UNDER COVER! KARYA NORAH VINCENT - Anggreini, Icha Syari; Rumadi, Hadi; ', Syafrial (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack : The engineering femininity arises because of several reasons, one of the novels that lifted the story of the novel female perekayasan under cover! Norah Vincent's work. The problem that arises is